Ocular Choroidal Melanoma with Multisystemic Metastasis in a Bitch: Ocular Choroidal Melanoma with Multisystemic Metastasis in a Dog - Keil, Eduarda; Lopes Simão, Beatriz; Ribeiro, Cibele; Oliveira Mirapalhete, Claudia; Mollerke Norte, Diego; Oliveira da Silva, Guilherme; Müller da Silva, Taiara; Barreto Coelho, Ana Carolina (Acta Scientiae Veterinariae, 2025)
Background: Melanoma is a type of cancer that originates from melanocytes in the neuroectodermal leaflet. Melanocytic tumors are the most common primary cancers of the eye in dogs. In addition, malignant intraocular melanoma accounts for approximately 15% of eye tumors in dogs, usually developing in the iris or ciliary body of the anterior uvea, and rarely in the choroid. Although systemic metastasis of ocular melanoma is uncommon, we report a case of multisystemic metastasis in a bitch with ocular melanoma in the choroid and iris, describing its clinical and pathological characteristics. Case: A 12-year-old bitch of no defined breed, weighing 27 kg, was referred to the Veterinary Medical Complex of the Centro Universitário Ritter dos Reis. She had a history of a significant increase in volume in the region of the left eye, with bloody discharge. The clinical signs reported were prostration, oscillating with moments of agitation, fever, vomiting, loss of appetite, with episodes of hypoglycemia even after feeding by nasoesophageal tube, and pale mucous membranes. Her respiratory and heart rates and body temperature were within normal standards. Hematological and biochemical tests showed mild anemia and slightly increased urea, creatinine, and chlorine levels. An abdominal ultrasound showed alterations suggestive of gastritis and a toxemic liver. Facial X-rays showed soft tissue mass in the left orbital region, with no bone involvement. An ultrasound of the eye revealed a dense, hyperechogenic nodular formation with cavities. Cytology confirmed a melanocytic tumor. Due to the patient’s poor prognosis and deteriorating clinical condition, euthanasia was performed, followed by a necropsy and histopathological examination. Macroscopically, the left ocular bulb exhibited a diffusely blackened cornea with focal ulceration. Cross-sectioning revealed a blackened, slightly granular, and shiny nodule with white areas measuring 3 cm, involving internal ocular structures and resulting in loss of definition. Additionally, black spots were observed on the surface of the lungs, kidneys, and heart. In the kidneys and myocardium, white nodules were also present in the cortical layer and heart muscle, respectively. The brain displayed a firm, irregular 1.2 cm nodule located at the optic chiasm, which, upon sectioning, resembled the nodule within the ocular bulb. Histopathological examination of the ocular bulb revealed a neoplastic proliferation of melanocytes arranged in a moderately dense mantle, extending throughout the choroid, adjacent adipose tissue, and iris. Similar neoplastic proliferation was identified in the lungs, kidneys, heart, and optic chiasm, consistent with melanoma metastasis. These histopathological findings supported a morphological diagnosis of diffuse, well-differentiated melanoma. This led to a morphological diagnosis of diffuse well-differentiated melanoma in the choroid and iris, with metastasis in the lungs, kidney, heart, and optic chiasm. Discussion: Melanoma is common in dogs but rare in other domestic species, affecting adult to elderly dogs between 7 and 11 years old. In this case, the histopathological features were consistent with primary ocular bulb melanoma, which accounts for approximately 15% of ocular neoplasms in dogs. These tumors exhibit a loss of cellular differentiation and are classified as amelanotic in approximately 1/3 of canine melanoma cases. In this case, the tumor developed in the less common areas of the choroid and iris. Systemic metastases were also reported, with neoplastic proliferation in unusual locations such as the optic chiasm, kidneys, and heart. In the kidneys and heart, the melanocytes lacked pigment, as was partially observed in the eyeball and optic chiasm, demonstrating a loss of cell differentiation and being classified as amelanotic. Keywords: metastasis, ocular neoplasm, ophthalmology, central nervous system. Título: Melanoma ocular em coroide com metástase multissistêmica em uma cadela Descritores: metástase, neoplasia ocular, oftalmologia, sistema nervoso central